An updated meta-analysis of the relationship between vitamin D levels and precocious puberty - Cheng, Hong; Chen, Dan; Gao, Hui (Frontiers in Endocrinology, 2023)
Background: Some studies have investigated the association between vitamin D levels and precocious puberty (PP), but with limited sample size and inconsistent conclusion across studies.: Until July 2022, a comprehensive electronic search on literatures was conducted in MEDLINE, Web of Science and CNKI (Chinese National Knowledge Infrastructure). A systematic review and meta-analysis of 15 case-control studies with 2145 cases and 2063 controls to explore the relationship between vitamin D and PP. Stratified analyses by year of publication, country, diagnosis category of PP, child's sex, and methods of 25(OH)D test were conducted.Results: There was a negative correlation between 25(OH)D concentrations and PP in all study populations (SMD = -1.046, 95%CI = -1.366, -0.726). The pooled SMD remained significant in Chinese studies (SMD = -1.113, 95%CI = -0.486, -0.741), studies published before or after 2018 (SMD = -0.9832 and -1.185, 95%CI = -2.044， -1.133 and -1.755， -0.726), studies with female children (SMD = -1.114, 95%CI = -1.446, -0.781), and studies using electrochemiluminescence to detect 25(OH)D (SMD = -0.999, 95%CI = -1.467, -0.531), etc. Vitamin D deficiency also increased the risk of PP (OR = 1.531, 95%CI = 1.098, 2.134). Unfortunately, heterogeneity was high in all analyses, and there were some publication bias.This systematic review and meta-analysis demonstrated an association between vitamin D and precocious puberty. We recommend more high-quality studies, especially prospective cohort studies with big sample size or some randomized controlled intervention trials, to validate the reliability of the results.